The nexus between blockchain distributed ledger technology and financial crimes - Newton Chinyamunjiko; Forbes Makudza; Lucia Mandongwe (International Journal of Financial, Accounting, and Management, 2022)
Purpose: The study sought to uncover the effect of blockchain digital ledger technology (BCDLT) on financial crimes. The study was driven by the need to promote blockchain technology in a bid to enhance financial sanity through elimination of financial delinquency. Research methodology: The study followed a quantitative paradigm using an explanatory research design. The study targeted financial executives, senior staff members at the Zimbabwe stock exchange, bankers and officials from the financial regulators. Data was collected using a structured questionnaire. Results: The study found out that of the four independent BCDLT antecedents, manual audit costs were insignificant, whereas the other three had strong positive associations with financial crime reduction. Limitations: The study targeted a specific group of financiers; hence the results may not be universal to other excluded categories Contribution: The study significantly guides policy formulation and laws in line with the adoption of the blockchain technology in the global financial system to guard against the possibility of new forms of financial crimes that could emanate from the use of technology.